Awareness of eating among college students for the health of future generations: University Students' Awareness of Eating - Kasap, Murat; Tutkun, Erkut (Progress in Nutrition, 2023)
Abstract. Background and aim: The purpose of this study is to investigate the eating awareness levels of undergraduate university students. The sample for the study comprised of 400 volunteer students from various faculties at Bursa Uludağ University who were chosen at random. Methods: The Eating Awareness Scale-30 (EAS-30), which was adapted to Turkish by Köse et al. (2016) and analyzed for reliability-validity, was used as a data collection tool in the study. The study group's data; normality distribution, T-Test in pairwise comparisons, Anova analysis in three or more comparisons, and Pearson correlation comparison in cause-effect comparisons were all examined at the p